Heterologous expression of Aspergillus aculeatus endo-polygalacturonase in Pichia pastoris by high cell density fermentation and its application in textile scouring. Issue 1 (December 2017) - Abdulrachman, Dede; Thongkred, Paweena; Kocharin, Kanokarn; Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Champreda, Verawat; Eurwilaichitr, Lily; Suwanto, Antonius; Nimchua, Thidarat; Chantasingh, Duriya
Abstract Background Removal of non-cellulosic impurities from cotton fabric, known as scouring, by conventional alkaline treatment causes environmental problems and reduces physical strength of fabrics. In this study, an endo-polygalacturonase (EndoPG) fromAspergillus aculeatus produced inPichia pastoris was evaluated for its efficiency as a bioscouring agent while most current bioscouring process has been performed using crude pectinase preparation. Results The recombinant EndoPG exhibited a specific activity of 1892.08 U/mg on citrus pectin under the optimal condition at 50 °C, pH 5.0 with a Vmax and Km of 65, 451.35 μmol/min/mL and 15.14 mg/mL, respectively. A maximal activity of 2408.70 ± 26.50 U/mL in the culture supernatant was obtained by high cell density batch fermentation, equivalent to a 4.8 times greater yield than that from shake-flask culture. The recombinant enzyme was shown to be suitable for application as a bioscouring agent, in which the wettability of cotton fabric was increased by treatment with enzyme at 300 U/mL scouring solution at 40 °C, pH 5.0 for 1 h. The bio-scoured fabric has comparable wettability to that obtained by conventional chemical scouring, but has higher tensile strength. Conclusion The work has demonstrated for the first time functions ofA. aculeatus EndoPG on bioscouring in eco-textile processing. EndoPG alone was shown to possess effective scouring activity. High expression level and homogeneity could be achieved in bench-scale bioreactor.